Effects of Bunium persicum (Boiss.) Essential Oil on the Contractile Responses of Smooth Muscle (An in vitro Study) - Farshad Kheiri; Bahram Dalir-Naghadeh; Massoud Maham; Ghader Jalilzadeh-Amin (Veterinary Research Forum, 2011)
Bunium persicum (Boiss.) is an economically important medicinal plant growing wild in arid regions in Iran. The essential oil of B. persicum (EOBP) was extracted using hydrodistillation. A total of eighteen compounds, representing 96.14 % of the oil was identified by gas chromatography/mass spectrometry (GC/MS).The main compounds were cuminaldehyde (23.04 %), gamma-terpinene (14.48 %), trans-3-Caren-2-ol (12.51 %), acetic acid (10.90 %) and 1,3,8 -p- menthatriene (7.89 %). The effects of 0.1 to 1000 g mL-1 EOBP on ruminal and abomasal smooth muscle of twenty-four healthy sheep and ileum preparations of six rats were assessed in vitro. Ruminal preparations showed relaxation (P < 0.05) when exposed to 100 - 1000 g mL-1 concentrations of EOBP. In the isolated abomasal preparations, EOBP (0.1 - 1 g mL-1) represented a weak spasmogenic effect followed by relaxation. The spontaneous contraction of abomasal smooth muscles was completely abolished with a high dose (1000 g mL-1) of EOBP. Five-minute incubation with EOBP, significantly (P < 0.05) inhibited Ach-induced contraction in higher doses on both tissues. In contrast, rat ileum only showed dose-dependent relaxation effect, and pre-incubated tissues with EOBP, decreased the Ach-induced contraction. The data indicated that the plant contained spasmogenic and spasmolitic constituents. The results also showed that the EOBP profoundly alters gastrointestinal smooth muscle contraction in a dose-dependent and tissue-specific manner.